Integrative analysis of ATAC-seq and RNA-seq for cells infected by human T-cell leukemia virus type 1. - Azusa Tanaka; Yasuhiro Ishitsuka; Hiroki Ohta; Norihiro Takenouchi; Masanori Nakagawa; Ki-Ryang Koh; Chiho Onishi; Hiromitsu Tanaka; Akihiro Fujimoto; Jun-Ichirou Yasunaga; Masao Matsuoka (PLoS Computational Biology)
Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy (HAM) after a long latent period in a fraction of infected individuals. These HTLV-1-infected cells typically have phenotypes similar to that of CD4+T cells, but the cell status is not well understood. To extract the inherent information of HTLV-1-infected CD4+ cells, we integratively analyzed the ATAC-seq and RNA-seq data of the infected cells. Compared to CD4+T cells from healthy donors, we found anomalous chromatin accessibility in HTLV-1infected CD4+ cells derived from ATL cases in terms of location and sample-to-sample fluctuations in open chromatin regions. Further, by focusing on systematically selected genes near the open chromatin regions, we quantified the difference between the infected CD4+ cells in ATL cases and healthy CD4+T cells in terms of the correlation between the chromatin structures and the gene expressions. Based on a further analysis of chromatin accessibility, we detected TLL1 (Tolloid Like 1) as one of the key genes that exhibit unique gene expressions in ATL cases. A luciferase assay indicated that TLL1 has an isoform-dependent regulatory effect on TGF-β. Overall, this study provides results about the status of HTLV-1-infected cells, which are qualitatively consistent across the different scales of chromatin accessibility, transcription, and immunophenotype.